Case Report: Complete Remission With Anti−PD−1 and Anti−VEGF Combined Therapy of a Patient With Metastatic Primary Splenic Angiosarcoma - Xu, Weiran; Wang, Kai; Gu, Wenguang; Nie, Xinxin; Zhang, Hao; Tang, Chuanhao; Lin, Li; Liang, Jun (Frontiers in Oncology, 2022)
Primary splenic angiosarcoma (PSA) is a rare malignancy with poor prognosis. At present, little study is available on immunotherapy in PSA. Here, we report a case of a patient with metastatic PSA who was treated with programmed death-1 (PD-1) inhibitors and vascular endothelial growth factor (VEGF) tyrosine kinase inhibitors combined therapy and achieved complete response (CR). The patient was a 57−year−old woman with three liver metastases. She was treated with seven cycles of toripalimab plus anlotinib. Programmed death-ligand 1 (PD-L1) immunohistochemistry and next-generation sequencing was performed, and the PD-L1 tumor proportion score was 75%. Finally, she achieved CR after six cycles of the combined therapy regimen. No serious adverse events were detected. To the best of our knowledge, this is the first clinical evidence that anti-PD-1 plus anti-VEGF therapy might be a promising option for patients with metastatic PSA. However, more clinical trials are needed to verify this conclusion.